Utrata ciąży jako wyzwanie dla kobiecości - analiza doświadczeń kobiet znajdujących się w sytuacji utrudnionej prokreacji = Miscarriage as a challenge for femininity - analysis of experiences of women with constricted procreation - Walentynowicz-Moryl, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to establish in what way the experience of constricted procreation and miscarriage influence the perception of one`s own femininity. The author uses the statements of twenty women, obtained by her in qualitative interviews based on dispositions in selected thematic areas. The respondents were patients of an Infertility Diagnostic Centre in a city district or users of Internet Forums dedicated to problems of constricted procreation. The analysis of different experiences of constricted procreation makes it possible to identify changes occurring in respondents` attitudes towards maternity - from the time they were not even planning to have a baby, through the time of procreation activities, up to the period of diagnosis and treatment. These changes went from treating maternity as one of the assumed contingents and obvious elements of future plans, to increasing concentration on reaching this aim.
Keywords: ograniczona prokreacja; poronienie; kobiecość; constricted procreation; miscarriage; femininity